THE EFFECT OF GENDER IN THE BOARD OF COMMISSIONERS ON COMPANY VALUE WITH FAMILY CONTROL AS A MODERATION VARIABLE IN INDONESIA - Limbago, Elsa; Sulistiawan, Dedhy (Review of Management and Entrepreneurship, 2019)
Gender has been a concern in the last ten years because gender differences have an impact on communication within the company so that it can affect the value of the company. The majority of companies listed on the IDX are family companies which will have an impact on the composition in the election of the company board. The results of previous studies on the influence of gender are also still inconsistent. This study aims to know the effect of gender on the board of commissioners on firm’s value and the influence of family control in weakening the influence of gender on the board of commissioners on firm’s value. Firm value was measured by using Tobin's Q, PBV and PER. The control variables used were firm size, commissioner size and leverage. The sample used in this research were all companies listed on the IDX except the financial and banking sectors and analyzed using multiple linear regression. The results proved that gender in the board of commissioners has no significant effect on firm value and there is no significant influence on family control in weakening the influence of gender on the board of commissioners on firm value.